MENGANALISIS KESIAPAN MADRASAH MENGHADAPI ASESSMEN KOMPETENSI MADRASAH INDONESIA: STUDI DI MADRASAH TASNAWIYAH NEGERI 2 KOTA BEKASI - Eka Oktaviani (Balai Diklat Keagamaan Bandung, 2023)
Indonesia's education system has changed and developed for the better. In the Ministry of Religious Affairs, this was marked by the existence of the Indonesian Madrasah Competency Assessment (AKMI). The assessments given include reading literacy, numeracy literacy, science literacy, socio-cultural literacy, and character surveys. MTSN 2 Bekasi City in 2022 got the first opportunity to implement the assessment. The researcher used the field research to qualitatively analyze the readiness of MTSN 2 Bekasi City in facing AKMI, such as the readiness of facilities and infrastructure, teacher readiness, and student readiness, as well as the obstacles faced in implementing the assessment. From this research, the readiness of facing AKMI was about 80%. This is also evidenced by the AKMI’s report card which is on average of capable and developing. The rest 20% are obstacles faced by the madrasah in terms of inadequate rooms, computers, as well as other technical obstacles. The results are also evaluation material for the madrasah so that in the future AKMI will be prepared very carefully to minimize existing obstacles. This includes serving as a resource for teachers to provide additional stimulation and mentoring to students who are still at a fundamental level, so that they may become more capable and skilled by providing a space for creativity.